Karoo Diary: 1 September to 30 November 2025 - Nicol, Martin (New Agenda: SA Journal of Social and Economic Policy, 2025)
A selection of events about, and from across, the Karoo that are significant or interesting, or both. Compiled by the New Agenda Editorial Collective at the Institute for African Alternatives and the Guest Editor.